Mixing viscoplastic fluids in stirred vessels over multiple scales: An experimental and CFD approach - Russell,AW; Kahouadji,L; Mirpuri,K; Quarmby,A; Piccione,PM; Matar,OK; Luckham,PF; Markides,CN (Chemical Engineering Science, 2019)
Dye visualisation techniques and CFD are used to characterise the flow of viscoplastic CarbopolTM solutions in stirred vessel systems over multiple scales. Centrally-mounted, geometrically-similar Rushton turbine (RT) impellers are used to agitate various Carbopol 980 (C980) fluids. The dimensionless cavern diameters, Dc/D, are scaled against a combination of dimensionless parameters: Rem-0.3Rey0.6n-0.1ks-1, where Rem, Rey, n and ks are the modified power-law Reynolds number, yield stress Reynolds number, flow behaviour index and impeller geometry constant, respectively. Excellent collapse of the data is demonstrated for the fluids and flows investigated. Additional data are collected using a pitched-blade turbine (PBT) with cavern size similarity being shown between the RT and PBT datasets. These results are important in the context of scale-up/scale-down mixing processes in stirred vessels containing complex fluids and can be used to show that flow similarity can be achieved in these systems if the processes are scaled appropriately.